Mesenchymal stem cell therapy and its application to bronchopulmonary dysplasia of the preterm neonate. A review - Gustavo Rocha (Publicaciones Permanyer, 2023)
Bronchopulmonary dysplasia (BPD) remains a significant contributor to the morbidity and mortality of infants delivered at very low gestational ages. The therapeutic approach to BPD is essentially preventive and supportive. Inflammation is the key contributor to the disease development. Mesenchymal cells (MSCs) have been described over 40 years ago and have been shown to possess potent anti-inflammatory and proangiogenic properties and to contribute to tissue regeneration in a variety of adult and children´s clinical diseases, leading to enthusiasm for their use in BPD. Preclinical animal studies and clinical trials in human preterm neonates point to a positive preventive, as well as reparative role in BPD. Recent work revealed that MSCs release extracellular vesicles, called exomes, that contain the therapeutic activity of MSCs. Several clinical trials on MSCs in BPD are currently taking place worldwide. This review briefly discusses the different types of stem cells, their clinical applications in paediatric contexts, with particular involvement in their use in BPD, and provides information on the current use of MSCs in BPD.